Deep Swift/UVOT Observations of GOODS-N and the Evolution of the Ultraviolet Luminosity Function at 0.2 < z < 1.2 - Alexander Belles; Caryl Gronwall; Michael H. Siegel; Robin Ciardullo; Mat J. Page (The Astrophysical Journal)
We present Swift Ultraviolet Optical Telescope (UVOT) observations of the deep field GOODS-N in four near-UV filters. A catalog of detected galaxies is reported, which will be used to explore galaxy evolution using UV emission. Swift/UVOT observations probe galaxies at z  ≲ 1.5 and combine a wide field of view with moderate spatial resolution; these data complement the wide-field observations of Galaxy Evolution Explorer and the deep, high-angular-resolution observations by Hubble Space Telescope. Using our catalog of detected galaxies, we calculate the UV galaxy number counts as a function of apparent magnitude and compute the UV luminosity function (LF) and its evolution with redshift. From the LF fits in various redshift bins, we calculate the star formation rate density as a function of redshift and find evolution consistent with past works. We explore how different assumptions such as dust attenuation corrections can dramatically change how quickly the corrected star formation rate density changes with redshift. At these low redshifts, we find no trend between UV attenuation and redshift or absolute magnitude with significant scatter in the UV spectral slope β . This data set will complement the extensive observations of GOODS-N already in the literature.